NITRATE CONTAMINATION OF GROUNDWATER BY AGRICULTURAL ACTIVITIES IN THE PROTECTED AREA OF COSTA DA CAPARICA (PORTUGAL) - Martinez, Jorge Luis; Mancuso, Malva Andrea; Ribeiro, Manuela Simões (Águas Subterrâneas, 2011)
This study comprised of an investigation of the nitrate (NO3-) contamination in a coastal aquifer within an area of 220 ha called Terras da Costa, an agricultural region spread along the Costa de Caparica, Almada municipality, Portugal. It was based on analytical results and aquifer hydraulic data collected in two sampling events (summer and winter) occurred in 2010. Four areas with NO3- concentrations in groundwater above 300 mg.L-1 were identified in both seasons, demonstrating direct correlation with agricultural practices observed in the region. Based on the results, groundwater was confirmed to be contaminated with concentrations above 50 mg.L-1 in up to 77% of the sampled wells during the dry season (summer).